Amorphous TiO2 nanofilm interface coating on mesoporous carbon as efficient sulfur host for Lithium–Sulfur batteries. (1st February 2020) - Liu, Shengtang; Li, Yaohua; Zhang, Ce; Chen, Xi; Wang, Zheng; Cui, Fangming; Yang, Xiaojing; Yue, Wenbo
Abstract: Lithium sulfur (Li–S) batteries are regarded as one of the most promising next-generation secondary batteries. However, the insulating nature of active materials, inevitable shuttle effect caused by dissolution of intermediate polysulfides, and severe volume expansion during lithiation prevent their practical application. Herein, we report a novel sulfur host composed of amorphous TiO2 nanofilm interfaces coating on mesoporous carbon by controlling the hydrolytic process of tetrabutyl titanate on the surface of 3D interconnect conductive carbon matrix. The sulfur host shows high surface area, considerable electrolyte wetting capability and strong absorption for lithium polysulfides. Owe to the rational design and outstanding properties, the sulfur cathode with the high active material content of ∼74% and mass loading of ∼3.2 mg cm −2 exhibits a high initial specific capacity of 1455 mAh·g −1 and maintained 1242 mAh·g −1 after 200 cycles at 0.1 C (1C = 1675 mAh·g −1 ) current density, and also delivers excellent long term cycling performance at 1 C with initial capacity of 720 mAh·g −1 and capacity remained up to 81% after 1000 cycles. Graphical abstract: Image 1